2017
DOI: 10.1038/nprot.2017.007
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated generation of multiple ocular-like cell lineages and fabrication of functional corneal epithelial cell sheets from human iPS cells

Abstract: We describe a protocol for the generation of a functional and transplantable corneal epithelium derived from human induced pluripotent stem (iPS) cells. When this protocol is followed, a proportion of iPS cells spontaneously form circular colonies, each of which is composed of four concentric zones. Cells in these zones have different morphologies and immunostaining characteristics, resembling neuroectoderm, neural crest, ocular-surface ectoderm, or surface ectoderm. We have named this 2D colony a 'SEAM' (self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 33 publications
(34 reference statements)
3
83
0
Order By: Relevance
“…*p < 0.05, **p < 0.01, and ***p < 0.001. viability varied by isoform, in all cases cells adhered, proliferated, and expressed pluripotency markers (Figures 1A and S1A-S1D). The typical four-zone SEAM structure seen previously, however, was only generated in the presence of LN511E8, the isoform employed in our published experiments ( Figure 1B) (Hayashi et al, , 2017. The other four isoforms, LN111E8, LN211E8, LN332E8, and LN411E8, supported the formation of SEAMs with distinct structural configurations.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…*p < 0.05, **p < 0.01, and ***p < 0.001. viability varied by isoform, in all cases cells adhered, proliferated, and expressed pluripotency markers (Figures 1A and S1A-S1D). The typical four-zone SEAM structure seen previously, however, was only generated in the presence of LN511E8, the isoform employed in our published experiments ( Figure 1B) (Hayashi et al, , 2017. The other four isoforms, LN111E8, LN211E8, LN332E8, and LN411E8, supported the formation of SEAMs with distinct structural configurations.…”
Section: Resultssupporting
confidence: 63%
“…Using E8 fragments of laminin-511 (LN511E8), we have generated hiPSC-derived colonies comprising four concentric cell zones, the emergence of which displays some similarities with ocular development (Hayashi et al, , 2017. We termed these types of colonies ''self-formed ectodermal autonomous multi-zones'' (SEAMs) of eye-like cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we discovered that CEC-specific PAX6 promoters are highly upregulated in LECs supplemented with KGF and Y-27632, which should be the key regulators of CEC differentiation and maintenance. We recently succeeded in inducing CECs from iPSCs cultured with KGF and Y-27632 11, 12 . Our findings provide strong evidence that LECs cultured with KGF and Y-27632 represent a better in vitro model for basic studies of CECs and could be widely utilized for translational research and clinical applications in regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these problems, alternative CECs are differentiated from different sources such as ex vivo -expanded limbal epithelial cells (LECs) 6, 7 , oral mucosal epithelial cells 8, 9 , and induced pluripotent stem cell (iPSC)-derived CECs 1012 . To make these alternative CECs equivalent to CECs in vivo , the culture system should be designed to maintain the characteristics of CECs in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the regenerated skin should be able to perform its original function and to develop appendages. We previously reported that progenitors of epidermal keratinocytes were generated from human induced pluripotent stem cells (PSCs) (Hayashi et al, , ). In addition, there have been some reports of keratinocyte lineages being induced from mouse (Bilousova & Roop, ) and human (Kogut, Roop, & Bilousova, ) induced PSCs.…”
Section: Introductionmentioning
confidence: 99%